2014
DOI: 10.1242/dev.100123
|View full text |Cite
|
Sign up to set email alerts
|

Eph-Ephrin signaling and focal adhesion kinase regulate actomyosin-dependent apical constriction of ciliary band cells

Abstract: Apical constriction typically accompanies inward folding of an epithelial sheet. In recent years there has been progress in understanding mechanisms of apical constriction and their contribution to morphogenetic processes. Sea urchin embryos form a specialized region of ectoderm, the ciliary band, which is a strip of epithelium, three to five cells wide, encircling the oral ectoderm and functioning in larval swimming and feeding. Ciliary band cells exhibit distinctive apical-basal elongation, have narrow apice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…As a default response to ephrin contact, cell contraction and cell-cell segregation rely on intact Eph tyrosine kinase activity and ADAM10-mediated proteolytic shedding of the interacting cell surface ephrin (Hattori et al, 2000;Janes et al, 2005Janes et al, , 2009, initiating signalling that modulates cytoskeletal and focal adhesion proteins (Nievergall et al, 2012;Pasquale, 2008). Emerging evidence suggests that Ephs can also be directly linked to the cortical actin cytoskeleton and to actin stress fibres (Salaita et al, 2010), and are involved in actinmyosin polymerisation (Krupke and Burke, 2014). However, molecular details of potential interactions between Ephs and cytoskeletal proteins, and mechanisms involved in relaying the effects of Eph clustering and transient kinase activation into a cytoskeletal reorganisation, remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As a default response to ephrin contact, cell contraction and cell-cell segregation rely on intact Eph tyrosine kinase activity and ADAM10-mediated proteolytic shedding of the interacting cell surface ephrin (Hattori et al, 2000;Janes et al, 2005Janes et al, , 2009, initiating signalling that modulates cytoskeletal and focal adhesion proteins (Nievergall et al, 2012;Pasquale, 2008). Emerging evidence suggests that Ephs can also be directly linked to the cortical actin cytoskeleton and to actin stress fibres (Salaita et al, 2010), and are involved in actinmyosin polymerisation (Krupke and Burke, 2014). However, molecular details of potential interactions between Ephs and cytoskeletal proteins, and mechanisms involved in relaying the effects of Eph clustering and transient kinase activation into a cytoskeletal reorganisation, remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, urchins have the simplest set: a single receptor and ligand. In urchins, Eph and Ephrin are expressed in broad domains of ectoderm, where they function at the interface to mediate apical contractility (Krupke and Burke, 2014). We now add to this a role in mediating aspects of dispersal and epithelial transition of migratory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of Sp-Efn was achieved using synthetic, capped mRNAs derived from the full length S. purpuratus Sp-Efn gene cloned in pCS2+ and transcribed using the SP6 mMessage mMachine kit (Ambion). 2–4 pL of a 0.2 μM injection solution was injected into each freshly fertilized egg as previously described (Krupke and Burke, 2014). Single blastomere injections followed Krupke et al (2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, I identified six TFs that are differentially expressed in four different species, some of which imply eumetazoan-specific (such as orthologs of TCF/Par), bilaterian-specific (such as Thr), or metazoan-specific conservation (such as Six1/2, Klf, Ezh, and Arx) , Otim et al 2004, Burke et al 2006, Peter and Davidson 2011, Tu et al 2012, Cui et al 2014, Krupke and Burke 2014, Barsi and Davidson 2016, which I identified as differentially expressed in all sampled deuterostome taxa, and is known to be important for larval ciliary bands in Strongylocentrotus (Barsi et al 2015, Barsi andDavidson 2016).…”
Section: Conserved Transcription Factors (Tfs) Are Differentially Expmentioning
confidence: 99%